PELAKSANAAN PEMBERDAYAAN MASYARAKAT BERBASIS RUKUN WARGA (PMB-RW) DI KOTA PEKANBARU - Sri Wahyuni; Zaili Rusli SD (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
The implementation of this program began by providing skills through training to citizens who became the target of implementing the PMB-RW program. There are still many activities that have not been implemented in the PMB-RW program. In addition to the activities that have not been carried out, activities that have been running have not been optimal as planned. In addition there are problems related to activities that must be prioritized. Activities that are carried out are still said to be activities that are not priority, due to a minimal budget. It has not improved the welfare of the community from the economic and social sectors which should be the goal of the implementation of the PMB-RW Program in the West Sidomulyo Village. With the knowledge and skills in these various fields, it can be one of the capital for the community to create new jobs. The research was carried out using descriptive qualitative research methods. This study uses the concept of community empowerment by Sumaryadi, namely: Independence, Progress, Welfare, Justice and Sustainability. This research data collection techniques that are carried out are abservation, interviews, documentation and literature study using descriptive analysis techniques. The implementation of the Community-Based Community Empowerment Program (PMB-RW) in the West Sidomulyo Village has not been able to improve the economic, social, community, but the knowledge of the community participating in the training has been obtained in the implementation of the PMB-RW Program. Participation of companion agencies has been running and has benefits for the implementation of the PMB-RW Program in planning and supervision. Community participation in the idea of activities has been carried out through deliberation, coordination and communication. However, the participation of funds is still limited by City goverment so that the planned activities cannot run all. The factors that influence the implementation of Community Based Community Empowerment Program (PMB-RW) in West Sidomulyo Village are the participation in the form of funds and energy/ideas in the form ideas and justice. Funds for the implementation of activities that will affect the implementation so that the participation of counterpart workers and ideas of ideas goes according to the wishes of the community. So that the ongoing justice in the implementation of this program.Keywords: Community Empowerment, Development